2001
DOI: 10.1002/1521-4028(200110)41:5<269::aid-jobm269>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Biomass production and secretion of hydrolytic enzymes are influenced by the structural complexity of the nitrogen source inFusarium oxysporumandAspergillus nidulans

Abstract: The structural complexity of the nitrogen sources strongly affects biomass production and secretion of hydrolytic enzymes in filamentous fungi. Fusarium oxysporum and Aspergillus nidulans were grown in media containing glucose or starch, and supplemented with a nitrogen source varying from a single ammonium salt (ammonium sulfate) to free amino acids (casamino acids), peptides (peptone) and protein (gelatin). In glucose, when the initial pH was adjusted to 5.0, for both microorganisms, higher biomass productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Earlier studies reported on the effect of media composition complexity, in particular in reference to the nitrogen source on various metabolic processes 10,12,20,27,31,32,43,45 . Supplementation of the medium with complex constituents always improved cellular metabolism.…”
Section: (-7'977-32mentioning
confidence: 78%
See 1 more Smart Citation
“…Earlier studies reported on the effect of media composition complexity, in particular in reference to the nitrogen source on various metabolic processes 10,12,20,27,31,32,43,45 . Supplementation of the medium with complex constituents always improved cellular metabolism.…”
Section: (-7'977-32mentioning
confidence: 78%
“…Supplementation of the medium with complex constituents always improved cellular metabolism. In addition to the studies already discussed in this paper, the complexity of the medium supplementation was reported to interfere with specific metabolic pathways, such as control of glycogen metabolism in yeast 12 , secretion of enzymatic activities 10,20,27,31,32,43,45 , primary 1 and secondary metabolites 9 . The effect induced by specific kinds of peptides on metabolic routes of nitrogen and carbon metabolism was also considered.…”
Section: (-7'977-32mentioning
confidence: 85%
“…In addition to the studies already discussed in this paper, the complexity of the medium supplementation has been reported to interfere with specific metabolic pathways, such as control of glycogen metabolism in yeast 11 , secretion of enzymatic activities 9,17,25,[28][29][30]40,42 , primary 1 and secondary 8 metabolites. The effect induced by specific kinds of peptides on metabolic routes of nitrogen and carbon metabolism have also been considered.…”
Section: Discussionmentioning
confidence: 99%
“…The dependence of polygalacturonase activity on the nitrogen source was described. The influence of the structural complexity of the nitrogen source on the biomass production and secretion of hydrolytic enzymes was described in Fusarium oxysporum and Aspergillus nidulans (da Silva et al, 2001) as well as on the yeast growth and fermentation (da Cruz et al, 2002). The results obtained with A. pullulans showed that the variations in activities of polygalacturonase were in the first 24 h of cultivation caused by production of different forms of enzyme (Fig.…”
Section: Resultsmentioning
confidence: 88%